Interference effects in the plasmon fields excited by a diatomic molecule - Segui Osorio, Silvina Inda Maria (2015)
We study the fluctuations of the plasmon field associated to the wake potential generated by a dimer formed by two identical charged particles (such as two nuclei of the ionized hydrogen molecule) traveling through a semiinfinite dielectric medium. We use coherent states to describe bulk and surface plasmons as wave packets that raise fluctuations in the electronic density of the material. We analyze different configurations of interest, taking into account various trajectories and orientations of the dimer.